2019
DOI: 10.1249/mss.0000000000001873
|View full text |Cite
|
Sign up to set email alerts
|

pQCT- and Ultrasound-based Muscle and Fat Estimate Errors after Resistance Exercise

Abstract: Purpose Resistance exercise increases blood flow, induces osmotic and hydrostatic fluid shifts during and immediately after exercise, and may trigger inflammatory responses for several days in the working muscle. The resultant muscle swelling can subsequently affect muscle size and quality assessments. However, the effects of muscle swelling on x-ray attenuation of adipose estimate errors are unknown. Methods Peripheral quantitative computed tomography … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 37 publications
0
18
0
1
Order By: Relevance
“…Lastly, it has recently been shown that unaccustomed resistance exercise can cause errors in ultrasound‐based measures 72 hours post‐exercise 48 . However, it should be noted that our participants were previously accustomed to the resistance exercise and we assessed a different muscle (pectoralis major) than the one assessed by Rowe et al 48 (biceps brachii), which likely limited the impact of this issue on our findings. Thus, whether a 72 hours post‐exercise ultrasound measure of the pectoralis major muscle can be affected by the acute effect of resistance exercise in previously accustomed subjects should be assessed in future studies.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Lastly, it has recently been shown that unaccustomed resistance exercise can cause errors in ultrasound‐based measures 72 hours post‐exercise 48 . However, it should be noted that our participants were previously accustomed to the resistance exercise and we assessed a different muscle (pectoralis major) than the one assessed by Rowe et al 48 (biceps brachii), which likely limited the impact of this issue on our findings. Thus, whether a 72 hours post‐exercise ultrasound measure of the pectoralis major muscle can be affected by the acute effect of resistance exercise in previously accustomed subjects should be assessed in future studies.…”
Section: Discussionmentioning
confidence: 85%
“…Fourthly, it should be acknowledged that daily 1RM estimations may not be accurate 18 . Lastly, it has recently been shown that unaccustomed resistance exercise can cause errors in ultrasound‐based measures 72 hours post‐exercise 48 . However, it should be noted that our participants were previously accustomed to the resistance exercise and we assessed a different muscle (pectoralis major) than the one assessed by Rowe et al 48 (biceps brachii), which likely limited the impact of this issue on our findings.…”
Section: Discussionmentioning
confidence: 99%
“…Although echo intensity is used as a marker for changes in muscle quality [7][8][9][10][20][21][22][23][24][25][26][27], studies using changes in echo intensity as a proxy have produced inconsistent results following resistance training (Table 1). Echo intensity has been reported to decrease [7, 20-24, 26, 27, 46], increase [25,27,57], or remain unchanged [8-10, 21, 27, 44-46, 64] following repeated bouts of resistance exercise. Using the traditional definition, a decrease in echo intensity should correspond to an increase in muscle strength per unit of muscle mass [9,20].…”
Section: Muscle Qualitymentioning
confidence: 99%
“…Echo intensity is determined by drawing a region of interest on the ultrasound image without including subcutaneous fat or bone. This region of interest may be a pre-specified sized box [3, 31, 33, 36, 40, 42, 48-51, 53, 54], a box containing as much of the muscle as possible [4,7,8,10,20,23,24,27,35,37,57,58], or free hand tracings between the adipose tissue and bone [9,15]. The majority of studies on echo intensity use a scale between 0 (black) and 255 (white) [4,20,24] or 0 (black) to 256 (white) [29,31,34].…”
Section: Introductionmentioning
confidence: 99%
“…Acute and chronic changes in EI have been observed with exercise. However, further experimental work is needed to provide appropriate interpretations of these changes in physiological and clinical contexts (Routledge et al 2019;Rowe et al 2019;Wong et al 2020). The omission and/or inappropriate accounting of the effects of subcutaneous fat on EI might partly explain inconsistent results in skeletal muscle tissue quality following resistance training reported in a recent review (Wong et al 2020).…”
Section: <<< Figure 2 >>>mentioning
confidence: 99%